Relationship Between Birth Weight and Asthma Diagnosis: A Cross-Sectional Survey Study Based on the National Survey of Children’s Health in the U.S. - Wei Li; Tao Wang; Qianqian Zhang; Hao Chen; Ze Chen; Zhiwei Liu; Meng Ni; Baihe Li; Jiuru Zhao; Sudong Qi; Qianwen Shen; Dongting Yao; et al. (BMJ Open)
Objective To assess the association between birth weight and childhood asthma risk using data from the 2019–2020 National Survey of Children’s Health database.Design Cross-sectional study.Setting The USA.Patients A representative cohort of American children.Exposure The exposure of this study was birth weight regardless of gestational age. Birth weight was divided into three groups: <1500 g, 1500–2500 g and >2500 g.Main outcome measures Primary outcomes were parent-reported diagnosis of asthma.Method The Rao-Scott χ2 test was used to compare the groups. The main analyses examined the association between birth weight and parent-report asthma in children using univariable and multivariable logistic models adjusting for preterm birth, age, sex, race, family poverty, health insurance, smoking, maternal age. Subgroup analysis was performed based on interaction test.Results A total of 60 172 children aged 3–17 years were enrolled in this study; of these, 5202 (~8.6%) had asthma. Children with asthma were more likely to be born preterm, with low birth weight (LBW) or very LBW (VLBW). The incidence of asthma was the highest in VLBW children at 20.9% and showed a downward trend with an increase in birth weight class, with rates of 10.7% and 8.1% in the LBW and normal birthweight groups, respectively. Children with VLBW (OR 1.97; 95% CI 1.29 to 3.01) had higher odds of developing asthma in the adjusted analysis model. However, VLBW was only shown to be a risk factor for asthma among Hispanics, black/African-Americans and children between the ages of 6 and 12 years, demonstrating racial and age disparities.Conclusions VLBW increases the risk of childhood asthma; however, racial and age disparities are evident.